Investigation of Thermal Environment on Traditional Balinese Buidings - Perpustakaan UGM, i-lib ([Yogyakarta] : Unit Informasi Inovasi Proses Pembelajaran (UI2P2) Universitas Gadjah Mada, 2003)
Air conditioning is one of the most important factors that determine human comfort, especially in a hot and humid climate. The development of housing complex tends to increase in this decade, but the thermal environment and human response have not yet been analyzed reiv well. The aim of air conditioning in traditional Balinese houses is to create a compliable. healthy and stable thermal condition since some traditional Balinese buildings may not be suitable for inhabitants health and are passible to create several diseases, although less energy consuming. The improvisation of air conditioning systems in traditional Balinese houses by using passive thermal design is needed. especially when people considering energy saving. This paper trill describe the improvisation of air conditioning system by passive design in order to contribute mare effective control of the elll'ir011111e111, to improve the relationship between the artificial environment and â¢ Minion beeingS, and perhaps Can be used to developing the standard code of building design in Bali. Keywords Air conditioning. heat transferand traditional building